EFEKTIVITAS HASIL SMASH PADA KEJUARAAN LIGA BOLA VOLI SERI VI SE-KALIMANTAN BARAT - Ervionita, Ninda; Supriatna, Eka; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThis study aims to determine the effectiveness of the smash results in the Series VI Volleyball League Championship in West Kalimantan. This study is a descriptive percentage study using the survey method. The population in this study was a party of 8 female volleyball high school matches in the Series VI Volleyball League Championship in West Kalimantan. The sample in this study is the entire female high school volleyball smash. The technique of collecting data uses observation, observations are made every time a match takes place which is recorded using a camera. Retrieving data in this study using GPAI observation sheets, this GPAI contains scores from each predetermined indicator. The data taken is only focused on the smash.The results showed that there were 826 smash of women's high school volleyball teams from 8 matches in the Serie VI Volleyball League Series in West Borneo. The percentage of effectiveness of the smash is 27.72%. Whereas 48.91% smash rally and 23.36% smash dies. These results indicate that the smash done is greater than the percentage of smash to produce points.Keywords :Effectiveness, Volly Ball, Smash